PHOSPHATE BUFFER SALINE AS AN ALTERNATIVE DILUENT IN EXAMINATION OF ERYTHROCYTE SEDIMENTATION RATE WESTERGREEN METHOD - Alfia, Shofa; Nugraha, Gilang; Anggraini, Rahayu; Lukiyono, Yauwan Tobing (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
Background: 0.9% NaCl is the standard method for examining ESR with EDTA blood, it was found that PBS has properties comparable to 0.9% NaCl because the osmolarity and ion concentration of this solution is isotonic with human body fluids.Aims: This study was to determine the difference in LED results using PBS pH 7.2 and pH 7.4 with the results of examining LEDs using 0.9% NaCl Westergren method.Methods: This study used an experimental method with a static group comparison research design. The difference in the results of the LED examination using 0.9% NaCl as the control group and PBS pH 7.2 and pH 7.4 as the test group.Results: statistical tests showed that the average value of LED using 0.9% NaCl was 13.10 mm/hour, PBS pH 7.2 was 12.40 mm/hour and PBS pH 7.4 was 10.30 mm/hour. Based on the results of the One Way Anova test, the p-value was 0.528 and the Post Hoc test results on PBS pH 7.2 obtained a p-value of 0.959 and PBS pH 7.4 p-value 0.523. Conclusion: the results of examining the LED using both PBS pH 7.2 and PBS pH 7.4 diluents showed no difference in results with 0.9% NaCl diluent as the standard method. So there is a suggestion from researchers to use abnormal samples diluted with PBS pH 7.2 to 7.4.